Pengaruh Profitabilitas, Leverage, Likuiditas, dan Ukuran Perusahaan Terhadap Pembagian Dividen Pada Perusahaan Perbankan Konvensional yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2016-2020 - Grasintya Eka Novianingtyas; Batara Daniel Bagana (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study examines the effect of profitability, leverage, liquidity, and firm size ondividend distribution. This research was conducted on conventional bankingcompanies listed on the Indonesia Stock Exchange (IDX) using valid annualfinancial statements. The sampling method uses financial reports on the officialwebsite, namely www.idx.com with data for the period 2016 to 2020. Therelationship and or influence between variables is explained by the descriptivestatistical test method. The results showed that profitability, leverage, liquidity,and company size had a significant positive effect on dividend distribution inconventional banking companies listed on the Indonesia Stock Exchange (IDX)